Oyster culture in the Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
..An oyster culture project funded by Canada's International Development Research Centre (IDRC) has proved successful in Jamaica where ten entrepreneurs have adapted the technique developed by the Ministry of Agriculture. As more people show...